Application of methylotrophic yeast Pichia pastoris in the field of food industry - A review - Silva, Viviane C. [UNESP]; Peres, Maristela F. S. [UNESP]; Gattás, Edwil A. L. [UNESP] (My University, 2009)
Since ancient times, the utilization of yeasts by the man has a great impact on the socio-economic development. After the advent of the technology of recombinant DNA, great advances have occurred due to the acquisition of strains of mutant yeasts in the field of applied research, and Saccharomyces cerevisiae has soon been outstanding as an interesting candidate for the expression of heterologous proteins of biotechnological interest. As the time goes by other alternative systems of expression have been shown because they have advantages over Saccharomyces cerevisiae. Among those new systems, Pichia pastoris is outstanding as methylotrophic yeast capable of growing in a culture medium containing methanol as the only source of carbon and energy. The induction of production of glycerol-3-phosphate dehydrogenase (GPD, NAD+: oxido-redutase EC 1.1.1.8) by Pichia pastoris was accomplished in the medium containing methanol. One of the most important key parameters in Pichia pastoris expression system is the methanol concentration. Bibliographic reviews on the Pichia pastoris production system have shown that the best culture conditions vary according to the strain used and/or kind of heterologous protein desired to be expressed. Therefore, we have sought to develop a system, involving expression of glycerol-3-phosphate dehydrogenase in the yeast Pichia pastoris, for generating sufficient quantities of the enzyme in order to asses its potential value for use in various food bioanalytical determination. Dehydrogenases have been widely used in the enzymatic assays of diverse composites of industrial interest, being enclosed among them glycerol and a number of important bioanalytical applications.
Keywords: Culture medium; Expression; Glycerol-3-phosphate dehydrogenase; Optimization; Pichia pastoris; Yeast